التحولات الديمقراطية في العالم العربي: دراسة نظرية تاريخية مقارنه - عسعوسي، سعد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to study the democratic transformations in the world, focusing particularly on the events and revolutions in Arabian countries between 2011-2015. In this study, the researcher reviews the concepts associated with the democratic transformation process, distinguishing between them and the democratic development that occurs as a result of the democratic transformation process. The researcher also explores the historical experiences in the democratic transformation, and compares these historical experiences with the Arab world's experiences as the western democracy model is more prevalent in the world. The researcher believes that the Arab world is an integral part of the modern world, where most of regimes seek to achieve sustainable development and to push their people into democratic regimes yet have peaceful rotation of power. The researcher examines many studies on the subject of development and democratic transformation and development. However he did not comprehensively, cover the stages of democratic transformation in most of the Arab countries regimes, as these regimes came to power in different ways and in complicated international and regional situations. Through this research, the researcher tries to analyze the reasons behind the revolutions in those countries and the factors that led to these revolutions at the time. The researcher movers then to discuss the effect of democracy and its development in the societies; he found that there is no reproducible from that can be applied in all countries, and that each country has its own specificity according to the sets of values, systems and concepts each has and according to the people's belief in the democratic system. The results in this study cannot be diagnosed clearly as the event in some Arab countries (Yemen, and Syria) is still ongoing while other countries have reached internal understanding (Tunisia, and Libya). Thus, they are still unstable and unable to reach an agreement in the formation of an acceptable government for all parties and organization that emerged after the collapse of the ruling regimes.